Physical Chemistry of Aqueous Processing - Shamsuddin M.; Sohn H.Y. (My University, 2025)
In this article, we discuss the importance and significant roles of physicochemical principles in hydrometallurgy. We highlight how the exploitation of these principles improves the processing steps, namely leaching, production of suitable intermediates, precipitation and cementation. The roles of unit processes like ion exchange and solvent extraction in the concentration and purification of leach liquors and the separation of chemically similar elements in the leaching circuit are discussed with appropriate examples. Since the entire operation is carried out in aqueous media, the review incorporates a discussion on the stability of water in acidic, alkaline, oxidizing, and reducing conditions. © 2024 Elsevier Ltd. All rights reserved.